Androgenic potential of polish barley cultivars in anther culture in vitro - Kruczkowska, H.; Pawłowska , H.; Skucińska , B. (Plant Breeding and Seed Science, 2005)
The aim of the research was to assess the androgenic potential of 21 Polish cultivars of spring and winter barley. On average, a few green plants developed per 100 anthers. Cold pretreatment proved conducive to the formation of embryos/calli, while mannitol pretreatment favoured green plant development. The first embryos/calli formed on the induction medium developed most efficiently. The authors chose FHG medium supplemented with 1 mg/l BAP and 0.2 mg/l 2,4-D (induction of androgenesis) and FHG medium supplemented with 0.4 mg/l BAP and 3% maltose (plant development).